Combined therapy of cyclosporine A and mycophenolate mofetil for the treatment of birdshot retinochoroidopathy: a 12-month follow-up. Issue 5 (22nd February 2013) - Cervantes-Castañeda, Rene Antonio; Gonzalez-Gonzalez, Luis Alonso; Cordero-Coma, Miguel; Yilmaz, Taygan; Foster, C Stephen
Abstract : Purpose: To retrospectively report a 12-month follow up for combined therapy with systemic cyclosporine A (CSA) and mycophenolate mofetil (MM) in treatment of patients with birdshot retinochoroidopathy (BSRC). Participants: Ninety-eight eyes of patients who received CSA and MM for the treatment of BSRC were included in the study. Methods: All patients were followed for at least five visits during the study, or until treatment failure, or loss of follow-up. Clinical data were analysed using a Student paired t-test, Wilcoxon signed-rank test, McNemar's test, and Kaplan -Meier survival curve. Side effects related to therapy were also recorded. Main outcome measures included best-corrected logarithm of the minimum angle of resolution visual acuity, vitreous inflammation, fluorescein angiography pathologic features, and electroretinogram recordings. Results: Vitreous inflammation scores at baseline and at 1 year were statistically significantly reduced in both eyes (p<0.001; p=0.001). The presence of angiographic leakage at the 1-year follow-up was significantly reduced (p=0.004). However, the presence of cystoid macular oedema (p=0.32) and comparison of electroretinogram 30-Hz amplitude revealed no significant reduction between baseline and 1-year values for either eye (p=0.61, p=0.87); nonetheless, 30-Hz implicit times were statistically significantly shorter at the end of follow-up for both eyes (p<0.001, p=0.035). Thirty-one patients (67.4%) achieved inflammation control at the 1-year endpoint. Side effects were transient, and resolved after lowering or withholding IMT for a few weeks in the majority of patients. Conclusions: These results suggest that combined IMT with CSA and MM for BSRC is well tolerated and associated with long-term control of inflammation.